Impact of a surfactant on the electroactivity of proteins at an aqueous-organogel microinterface array - O'Sullivan, S.; Arrigan, Damien (American Chemical Society, 2013)
The impact of surfactant addition to the organic phase on the electroactivity of proteins at the aqueous-organogel interface was examined by voltammetry. The presence of bis(2-ethylhexyl)sulfosuccinate (AOT) in the organogel phase, as the sodium salt, caused marked changes in the peak currents for myoglobin detection. The protein desorption voltammetric peak exhibited a 6-fold increase in the current compared to the corresponding experiment without surfactant. Interfacial coverage showed a 17-fold increase in the adsorbed protein at the interface, from 50 pmol cm-2, in the absence of surfactant, to 850 pmol cm-2, in the presence of 10 mM surfactant. Additionally, the presence of the surfactant resulted in a second pair of adsorption/desorption peaks at lower potentials and in a change in the capacitance of the system. The formation of surfactant-protein and surfactant-protein-organic anion deposits is proposed on the basis of these features, leading to increased voltammetric signals for myoglobin, hemoglobin, and cytochrome c. The mechanism of protein-surfactant interaction was probed by using the surfactant as the anion in the organic phase electrolyte salt. Repetitive cyclic voltammetry of cytochrome c showed that in the presence of surfactant there was an enhancement of the signal, caused by a build-up of the protein-surfactant-electrolyte anion assembly at the interface. These findings provide the basis for surfactant-modified interfaces to enhance the electroanalytical performance for protein detection.